Pengaruh Label Halal dan Harga Terhadap Keputusan Pembelian Pada Produk Mixue : Studi pada Mahasiswa FEB UMSU - Rezza Asmara Putra; Satria Mirsya Affandy Nasution (Fisarrearch, 2023)
This research aims to find out how the halal label and price variables influence purchasing decisions, both partially and simultaneously, for Mixue products (case study of students at Muhammadiyah University, North Sumatra). This research approach is associative. The population is 100 users and the sample is 100 mixue consumers. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. It is partially known that the halal label has a significant influence on purchasing decisions for mixue products. In particular, it is known that price has a significant influence on purchasing decisions for mixue products. Simultaneously, it is known that the halal label and price have a significant influence on purchasing decisions for mixue products.Keywords: Halal Label, Price, Purchase Decision